Moderation Role of Tax Volunteer on Taxpayer Compliance in Indonesia - Rio Nyoman Bagaskoro; Nur Diana; Dewi Diah Fakhriyyah (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to analyze the influence of taxpayers and e-filing on taxpayer compliance and tax volunteers as a moderation study at KPP Pratama Singosari and KPP Pratama Batu. The research was carried out using a quantitative approach with a questionnaire as the research instrument. The research sample was 180 taxpayers using an incidental sampling technique. Data analysis was carried out using moderated regression analysis using the SmartPls-3 program. The research results show that tax understanding, e-filing and tax volunteers have a significant positive effect on taxpayer compliance. Tax volunteers are not able to moderate the influence of taxpayer understanding on taxpayer compliance, but are able to moderate the influence of the use of e-filing on taxpayer compliance. The results of this study are expected to provide the development of theory planned behavior considering that behavior will continue to change along with the development of science and technology. The results of the study are also expected to add insight into the implementation of compliance theory in social life, especially related to taxpayers.